2023
DOI: 10.3390/machines11080833
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Mobile App with NAO Robot for Autism Education

A. M. Mutawa,
Hanan Mansour Al Mudhahkah,
Aisha Al-Huwais
et al.

Abstract: This paper aims to investigate the possibility of combining humanoid robots, particularly the NAO robot, with a mobile application to enhance the educational experiences of children with autism spectrum disorder (ASD). The NAO robot, interfaced with a mobile app, serves as a socially assistive robotic (SAR) tool in the classroom. The study involved two groups of children aged three to six years old, exhibiting mild to moderate ASD symptoms. While the experimental group interacted with the NAO robot, the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…NAO is balanced by four pressure sensors that control the corresponding centre of pressure on each foot. It has four speakers and a speech recognition and analysis system, which allow it to listen, speak, and perform spatial acoustic positioning, and two high-definition CMOS cameras that enable forward vision; such powerful hardware endows NAO with a high degree of artificial intelligence [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NAO is balanced by four pressure sensors that control the corresponding centre of pressure on each foot. It has four speakers and a speech recognition and analysis system, which allow it to listen, speak, and perform spatial acoustic positioning, and two high-definition CMOS cameras that enable forward vision; such powerful hardware endows NAO with a high degree of artificial intelligence [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Throughout this review, research was found with all the types of robots mentioned ( Figure 2 ). Then, it was observed that, with humanoid robots themselves, the most widely used was NAO, which is used in approximately 30% of the research on social robots for autistic children [ 58 ]. Of the studies reviewed for this paper, the NAO robot was used in 44.44% of the cases.…”
Section: Discussionmentioning
confidence: 99%